Thiol–ene coupling reaction achievement and monitoring by "in situ" UV irradiation NMR spectroscopy. Issue 42 (2nd July 2020) - Toncheva-Moncheva, Natalia; Dangalov, Miroslav; Vassilev, Nikolay G.; Novakov, Christo P.
Abstract : An " In situ " LED UV illumination NMR setup for achievement of initiator-free coupling reactions of allyl-functionalized poly(allyl glycidyl ether) with polyethylene glycols thiols. Abstract : In this study, the possibilities of a new " in situ " LED UV illumination NMR spectroscopic technique for performing an initiator-free thiol–ene "click" coupling reaction of an allyl-functionalized poly(allyl glycidyl ether) (PAGE) prepolymer with a number of mono- and di-oligo polyethylene glycol (PEG) thiols is demonstrated. The state-of-the-art setup constructed with LEDs as UV light sources that illuminate through optical fibers directly into an NMR testing tube at a fixed wavelength of 365 nm is appropriate for various polymeric materials and biologically active substances. The selected experimental protocol uses a series of periods of irradiation and dark periods, thus providing opportunities to conduct an effective thiol–ene "click" reaction and simultaneously study the kinetics of the photochemical reaction with the exposure time, as well as macromolecular association directly in a solution applying the whole types of NMR methods: from conventional 1 H or 13 C NMR to diffusion NMR spectroscopy (DOSY). In addition, the molecular mass characteristics of the prepared copolymers were studied by gel-permeation chromatography (GPC). The observed differences in the reaction rates as well as in the size of species formed (the corresponding hydrodynamic radiuses R h of aggregates) as a result of the coupling process of parent PAGE prepolymers and model PEG thiols were thoroughly discussed and the reaction pathway proposed.